Effectiveness of Classical Services with Jigsaw Technique to Improve Pancasila Student Profile in Madrasahs - Putri Dwi Oktavia; M. Fauzi Hasibuan (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2024)
Although various previous studies have examined the theme of Jigsaw as an active learning approach in the classroom, no one has examined it from the aspect of student character development. This study aims to analyze the effectiveness of classical services with Jigsaw techniques to improve the profile of Pancasila students in madrasah. The setting of this research is Madrasah Aliyah Negeri 3 Langkat, North Sumatra. This research used quantitative experimental method, by comparing the experimental group that received classical service with Jigsaw technique and the control group with conventional classical service. Data were collected through questionnaires and analyzed statistically. The results of this study showed a significant increase in students' empathic attitudes after treatment, with the experimental group showing a higher increase. Wilcoxon Signed Ranks Test and Kolmogorov-Smirnov 2 Independent Samples analysis confirmed the effectiveness of the Jigsaw technique (p < 0.05). The majority of experimental group students (88%) achieved the very high category in empathic attitude. This success was attributed to students' active participation, cooperative learning, and diverse interactions. Despite limitations, this study provides strong evidence of the effectiveness of the Jigsaw technique in improving empathic attitudes, contributing to the development of students' character and social skills as per the Pancasila Learner Profile.